Annealing-temperature-modulated optical, electrical properties, and leakage current transport mechanism of sol–gel-processed high-k HfAlOx gate dielectrics. Issue 3 (15th February 2017) - Jin, P.; He, G.; Fang, Z.B.; Liu, M.; Xiao, D.Q.; Gao, J.; Jiang, S.S.; Li, W.D.; Sun, Z.Q.; Zhang, M.
Abstract: Deposition of HfAlOx gate dielectric films on n-type Si and quartz substrates by sol-gel technique has been performed and the optical, electrical characteristics of the as-deposited HfAlOx thin films as a function of annealing temperature have been investigated. The optical properties of HfAlOx thin films related to annealing temperature are investigated by ultraviolet-visible spectroscopy (UV–vis) and spectroscopy ellipsometry (SE). By measurement of UV–vis, average transmission of all the HfAlOx samples are about 85% owing to their uniform composition. And the increase in band gap has been observed with the increase of annealing temperature. Moreover, the increase of refractive index (n) and density with the increase of annealing temperature are obtained by SE measurements. Additionally, the electrical properties based on Al/Si/HfAlOx /Al capacitor are analyzed by means of the high frequency capacitance-voltage ( C-V ) and the leakage current density-voltage ( J-V ) characteristics. Results have shown that 400 °C-annealed sample demonstrates good electrical performance, including larger dielectric constant of 12.93 and lower leakage current density of 3.75×10 −7  A/cm 2 at the gate voltage of 1 V. Additionally, the leakage current conduction mechanisms as functions of annealing temperatures are also discussed systematically.